Analisis Pola Fungsi Kalimat dan Kesalahan Berbahasa Pada Teks Berita Dalam Website “CNN Indonesia” Edisi Januari 2024 Sebagai Sumber Bacaan dan Bahan Ajar Siswa Kelas XII - Ajeng Ayuningdyas; Laksmana Pujiatmoko; Mega Wahyu Ningrum; M. Farell Rachmadhani Zidan Saputra; Tri Widiyanto; Asep Purwo Yudi Utomo; Arum Yuliya Lestari (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to evaluate the structure of sentence function patterns and language errors in news texts published on the CNN Indonesia website in the January 2024 edition. The reason for this research stems from the need to understand the right sentence structure and appropriate language in the context of news to improve language skills in students, especially level XII. The method used in this analysis is by analyzing the data. Several stages are used in analyzing sentence patterns including reading news from online websites, reducing data according to theory, identifying, analyzing, formulating, and presenting the data obtained. This research focuses on sentence patterns and language errors that may occur. This analysis aims to identify commonly used sentence patterns and language errors that commonly occur when composing texts. The results show that there are errors in sentence function patterns and language errors, in language errors such as term usage, word usage, punctuation usage, sentence clarification, sentence repetition, and syntax errors, among others. This analysis provides a deeper understanding of the linguistic aspects that need to be considered when composing texts. The advantage of this research is that it provides useful learning materials for grade XII students to improve their understanding of sentence structure and grammar in news writing. The researcher hopes that with a deeper understanding of the correct use of language, students will be able to improve their writing skills.